Effect of ionic liquid anion and cation on the physico-chemical properties of poly(vinylidene fluoride)/ionic liquid blends. (October 2015) - Mejri, R.; Dias, J.C.; Lopes, A.C.; Bebes Hentati, S.; Silva, M.M.; Botelho, G.; Mão de Ferro, A.; Esperança, J.M.S.S.; Maceiras, A.; Laza, J.M.; Vilas, J.L.; León, L.M.; et al.
Graphical abstract: Highlights: Physico-chemical properties of PVDF/IL blends have been investigated. The effect of IL cation and anion in the blends is evaluated. PVDF β-phase content is promoted by the inclusion of IL. IL content also affects mechanical and electrical properties of the blend. Novel PVDF/IL blends are thus proposed for advanced applications. Abstract: Poly(vinylidene fluoride), PVDF, has been blended with different ionic liquids (IL) in order to evaluate the effect of the different IL anions and cations on the electroactive β-phase, thermal, mechanical and electrical properties of the polymer blend. [C2 MIM][Cl], [C6 MIM][Cl], [C10 MIM][Cl], [C2 MIM][NTf2 ], [C6 MIM][NTf2 ], [C10 MIM][NTf2 ] have been selected and were introduced in the polymer at a weight percentage of 40 wt%. It was found that the incorporation of ILs into the PVDF matrix leads to an increase of the β-phase content due to the strong electrostatic interactions between the dipolar moments of PVDF and the ILs. Further, the incorporation of ILs into PVDF strongly decreases the elastic modulus and increases the electrical conductivity of the blend with respect to the pure polymer matrix, all these effects being accompanied by a modification of the crystallization kinetics, as indicated by the modified spherulitic microstructure. Thus, novel PVDF/IL blends films with high transparency, excellent antistatic properties, and highly polar crystal form fraction were successfully achieved.